2018
DOI: 10.1108/raf-12-2016-0199
|View full text |Cite
|
Sign up to set email alerts
|

How does directors’ remuneration affect SMEs’ performance?

Abstract: Purpose -The purpose of this paper is to explain empirically the relationship between the remuneration levels of a sample of listed Small and Medium Enterprises (SMEs) directors and firm performance. The paper also investigates whether deviations from the optimal directors' remuneration level reduce firm performance.Design/methodology/approach -The study uses a panel data regression analysis of 802 AIMlisted SMEs over an eight-year period (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012).Findings -Using a non-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 107 publications
(129 reference statements)
3
21
1
Order By: Relevance
“…According to the findings of a study conducted by Mahmud et al (2018), remuneration has no significant effect on employee performance at Semarang State University. In contrast to the findings of (Agustiningsih et al, 2017;Calvin, 2017;Afrifa & Adesina, 2018;Nasution, 2019), which state that remuneration has a significant effect on employee performance as evidenced by a P-value greater than 0.05, this is what distinguishes the results of research by researchers.…”
Section: Discussioncontrasting
confidence: 59%
“…According to the findings of a study conducted by Mahmud et al (2018), remuneration has no significant effect on employee performance at Semarang State University. In contrast to the findings of (Agustiningsih et al, 2017;Calvin, 2017;Afrifa & Adesina, 2018;Nasution, 2019), which state that remuneration has a significant effect on employee performance as evidenced by a P-value greater than 0.05, this is what distinguishes the results of research by researchers.…”
Section: Discussioncontrasting
confidence: 59%
“…Way ( 2002) made another research in the USA on SMEs, and surveyed compensation divided into two parts: he found that group performance-based compensation was a key area of employee objectives, by which the attraction, motivation and retention of colleagues is more effective; also, the level of the basic salaryin comparison with the competitorshad an impact on the performance of organisations. Afrifa and Adesina (2018) said, concerning the SMEs operating in the United Kingdom, that the optimum level of the remuneration of managers should be supported and determined by HR systems, as they had clear impacts on their performance. Although company performance is influenced by several factors (structure, strategy), it can be demonstrated at Canadian SMEs that the application of the principle of "pay-for-performance" made a contribution to the enhancement of organisational performance (Wang et al, 2018).…”
Section: Compensation At Small and Medium-sized Enterprisesmentioning
confidence: 99%
“…However, according to agency theory, remuneration can limit agency problems and bridge the gap in interests between directors and shareholders. The assumption of agency theory is that companies design contracts for directors and managers with optimal incentives as their motivation to improve performance (Afrifa and Adesina, 2018).…”
Section: Directors' Remuneration On Roa and Pbvmentioning
confidence: 99%